Once Again about Women's Burials with Jewelry Tools from the Muroma Burial Grounds in the Lower Oka Region - Olga V. Zelentsova (Археология евразийских степей)
Burials of women with casting tools are a striking feature of the Finno-Ugric antiquities of the early Middle Ages. They are known in the burial grounds of the Muromians, Mordvins, Mari people in the V–IX centuries AD. These findings allowed the researchers to conclude that the women of these tribes were engaged in jewelry craft. The purpose of this article is to analyze new similar burials from the Podbolotyevo burial ground and determine the place of these women in Muroma society. A typological analysis of the most common objects – clay ladles for pouring molten metal, allowed us to identify the early types of this instrument, which have been used since the VI century. The discovery of a clay ladle with an iron rod in the burial, which are often found together, made it possible to identify the rod as the ladle handle and served to perform safe heating operations. The dynamics of changes in the burial ritual and inventory of such burials are traced, which allowed us to conclude that at the turn of the I-II millennium, changes took place in Muroma society, in which female foundry workers were also involved. The presence of coins in the burials, acting as a means of payment, as well as finding weighing tools in the foundry complexes suggest that foundries at that time were involved in commodity relations. The special position of these women in society and, probably, the fear of them led to the fact that after their death certain rituals were performed with their remains, which we record in the form of destruction of the headboard of the deceased.